Implementasi PjBL (Project Based Learning) untuk Meningkatkan Keaktifan Belajar pada Mata Kuliah Praktik Sensor dan Tranduser - Wahrini, Retyana (Edudikara: Jurnal Pendidikan dan Pembelajaran, 2023)
This research aims to determine the level of student activity in the Sensor and Transducer Practice course using the Project Based Learning (PjBL) learning model. The research carried out is Classroom Action Research (CAR). The subjects of this research were students in the Mechatronics Vocational Education study program, FT UNM, even semester, 2023/2024 academic year, with a total of 27 students. This research consisted of three cycles with two meetings in each cycle. Data collection techniques in this research used observation, learning outcomes tests, and documentation. The data analysis technique used is qualitative descriptive analysis. The research results showed that the average percentage of activity in cycle I based on observations was 72.00% and based on questionnaire data was 71.01%. So the average cycle I shows a result of 71.01%. The cycle is continued so that it runs better and optimally, this is an effort to improve the reflection results in cycle I. The average percentage of student activity in cycle II based on observations is 74.00 showing a result of 75.01%. The cycle continued to cycle III to prove that the improvement occurred due to the implementation of the Project Based Learning learning model. The average percentage of student activity in cycle III based on observations was 76.50% and based on questionnaire data was 77.00%. So the average cycle III shows a result of 76.60%.